(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article compares the clinical effectiveness of bloody and bloodless castration methods used in dogs. The study was conducted on 10 clinically healthy male dogs, and the animals were divided into two groups of 5. The first group received bloody (surgical) castration, and the second group received bloodless castration using a ZAN clamp. The general condition of the animals, pain response, wound healing process, and observed complications were evaluated in the postoperative period. According to the results of the study, despite the presence of an operational wound in the bloody castration method, wound healing and clinical recovery were relatively fast. The bloodless castration method was technically simple and convenient to perform, and was distinguished by a low risk of bleeding. At the same time, it was observed that the postoperative pain reaction lasted longer in the bloodless method. The results showed that when choosing a castration method in dogs, it is important to take into account the postoperative recovery process, pain level, and animal well-being.